PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Anggi Fitri; Firdaus Firdaus; Juni Kardi; Yundri Akhyar; Zalisman Zalisman; Syahri Ramadhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition learning model on students' reading comprehension skills. This research uses a quantitative approach with the type of research Quasy Experiment Design. Experimental research is research that is intended to determine whether or not there is a result of